2018
DOI: 10.1007/s40572-018-0173-4
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Exposures to Perfluoroalkyl Substances (PFASs): An Update of Associated Health Outcomes

Abstract: PFASs are persistent organic pollutants that have been widely produced and used in a range of commercial products since the 1950s. Human exposures to PFASs are nearly ubiquitous globally, but studies that addressed potential health effects of PFASs have only begun to accumulate in recent years. Animal studies suggest adverse effects resulting from developmental encompasses prenatal exposures to PFASs. In humans, the developing fetus is exposed to PFASs via active or passive placenta transfer, while newborns mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 182 publications
(83 citation statements)
references
References 135 publications
2
81
0
Order By: Relevance
“…Other cohort studies that investigated the associations regarding prenatal PFASs exposures on fetal growth indicators were mostly small in size and they only assessed PFOS or PFOA exposures [ 37 , 38 ]. Among the larger cohorts (i.e., >500 births), two also reported that prenatal PFOA and PFNA exposures were associated with lower average birth weights [ 16 , 17 ], while several others reported non-statistically significant associations [ 29 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other cohort studies that investigated the associations regarding prenatal PFASs exposures on fetal growth indicators were mostly small in size and they only assessed PFOS or PFOA exposures [ 37 , 38 ]. Among the larger cohorts (i.e., >500 births), two also reported that prenatal PFOA and PFNA exposures were associated with lower average birth weights [ 16 , 17 ], while several others reported non-statistically significant associations [ 29 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also excluded women reporting having hypertension, metabolic disorders, or chronic kidney diseases during pregnancy in the first telephone interview (n = 18 cases and 14 controls). We conducted stratified analyses for parity, maternal age, and socio-occupational status because these factors had previously been suggested to be associated with the risk for miscarriage in the DNBC (Feodor Nilsson et al 2014;Norsker et al 2012) and they could potentially modify the effect estimates of PFAS exposures (Chang et al 2016;Liew et al 2018a). Tests of heterogeneity were performed by assessing the p-value of the interaction term for each PFAS and potential modifying factors in the regression models.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, considerable amounts of PFAS from the mothers can cross the placental barrier and accumulate in the fetus (Fei et al 2007;Manzano-Salgado et al 2015). Numerous epidemiological studies have suggested that prenatal PFAS exposure might affect fetal growth (Bjerregaard-Olesen et al 2019;Fei et al 2008;Liew et al 2018a) and increase risk for preterm birth (Meng et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…PFAS exposure also affected birth outcomes controlled by thyroid hormone [161] and increased thyroid disease at general population exposure levels [162]. A recent systematic review identified evidence of a positive association between maternal levels of PFHxS, PFOS, and PFNA and maternal thyroid stimulating hormone (TSH) and a potential negative association with T4 [163].…”
Section: Modulates Receptor-mediated Effectsmentioning
confidence: 99%